Facial synthesis of highly active polymer vanadium molybdate nanocomposite: Improved thermoelectric and antimicrobial studies. (August 2019) - Khan, Anish; Parwaz Khan, Aftab Aslam; Khan, Imran; Oves, Mohammad; Khan, Shakeel; Asiri, Abdullah M.; Azum, Naved; Taib, Layla Ahmad; Al Angari, Yasser Mohammed; Facchetti, Antonio
Abstract: In this study, a novel poly(o-toluidine)V(III)molybdate (POT-V(III)MoO4 ) nanocomposite was prepared using a simple sol–gel strategy. The in situ polymerization of ortho-toluidine in the V(III)MoO4 framework was achieved by oxidation with ammonium persulfate. The material obtained was characterized by various techniques comprising scanning electron microscopy, Fourier transform-infrared spectroscopy, thermogravimetric analysis, X-ray diffraction, and X-ray photoelectron spectroscopy. Dielectric and AC conductivity studies were conducted to determine the physicochemical state of POT-V(III)MoO4 . The dielectric parameters ε ′, ε ″, tanδ, and σAC change with the capacity. The relationships between the dielectric properties ε ′, ε ″, tan δ, and AC conductivity (σAC) with the recurrence showed that the scattering was due to the Maxwell–Wagner type of interfacial polarization. Antibacterial tests of POT-V(III)MoO4 were performed using Gram-positive ( Enterococcus faecalis ) and Gram-negative ( Serratia marcescens ) bacteria, and the results indicated its excellent antimicrobial activity against both bacterial strains. Assessments of the antimicrobial activities in a liquid medium and on the solid surface of growth medium showed that a bacterial inhibition zone developed, and POT-V(III)MoO4 was more effective compared with the standard drug amoxicillin. Graphical abstract: Preparation of the composite.Image 1 Highlights: POT-V(III)MoO4 nanocomposite synthesized using facile method. Strong antibacterial effects on Gram-positive and Gram-negative bacteria. POT-V(III)MoO4 more effective than amoxicillin. POT-V(III)MoO4 composite has high AC conductivity and optical properties. Useful composite for applications in biological signaling devices.